Sikap dan Kepribadian Pendidik dan Peserta Didik dalam Al-Qur’an dan Hadis - Wasalmi Wasalmi; La Ode Amir Ifan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The Qur’an and Hadith, as the primary sources of Islamic teachings, provide a comprehensive value framework regarding the ideal character that should be possessed by both educators and learners. Educators are required to demonstrate sincerity, patience, justice, noble character, and to serve as role models (uswah hasanah) for their students. Education is a fundamental pillar in the formation of individual character and personality. This study aims to examine and analyze the concepts of attitudes and personality of educators and learners based on the Qur’an and Hadith. The method employed is a literature review using a qualitative approach through the analysis of relevant Qur’anic verses and Prophetic traditions. The results of the study indicate that learners are individuals who strive to develop their potential through the learning process within educational pathways, both formal and non-formal, at certain levels and types of education. Among the ethics of learners toward educators are sitting politely in front of the teacher, speaking respectfully, not interrupting the teacher while speaking, listening attentively to the teacher’s explanations, asking questions gently and respectfully when something is not understood, attending school regularly, avoiding truancy and lateness without valid reasons, entering the classroom promptly before the teacher arrives, and obeying the teacher’s advice.